The associatıon of p53 codon 72 polymorphism with thyroid cancer in Turkısh patients - (:unkn) unknown (My University, 2007)
Amaç: Tiroid kanseri en sık görülen endokrin malignitedir. Hastalığa yol açan moleküler mekanizmalar çeşitlilik göstermektedir. p53 geninin polimorfik varyantları ile çeşitli insan kanserleri arasındaki ilişki gösterilmiştir. Bunlar arasında kodon 72 en sık çalışılan varyanttır ancak tiroid kanseri ile ilgili sadece 2 çalışma mevcuttur. Bu çalışmada Türk hastalarda p53 kodon 72 polimorfizmi ile tiroid kanseri arasındaki ilişkinin araştırılması amaçlanmıştır. Materyal ve Metot: 58 tiroid kanser hastasının ve 115 sağlıklı bireyin genotip analizi PCR-RFLP yöntemi ile yapılmıştır. Sonuçlar: Polimorfik prolin allel sıklığı hastalarda kontrollerden daha yüksektir. Pro/Pro genotipi tirod kanser gelişimi için bir risk faktörü olarak bulunmuştur. Arg/pro genotip sıklığı açısından hasta ve kontrol grupları arasında farklılık bulunmamıştır. Foliküler adenom ve papiller karsinom hastaları veya papiller karsinom hastalarının TNM evrelendirmeleri açısından kodon 72 genotipleri açısından bir fark bulunmamıştır. Tartışma: Tiroid kanser gelişimine neden olan moleküler mekanizmaların aydınlatılabilmesi için farklı populasyonlarda kodon 72 polimorfizmi ile birlikte diğer genetik faktörlerin de çalışılmasına gereksinim vardır.

Objective: Thyroid cancer is the most common endocrine malignancy. Molecular mechanisms underlying this disorder are heterogeneous and need to be clarified. Different polymorphic variants of the p53 gene have been demonstrated to be in association with several human malignancies. Of those, codon 72 polymorphism is the most extensively studied variant; however, so far only two studies have investigated the association of this polymorphism with thyroid cancer. Thus, we aimed to investigate the association of p53 codon 72 polymorphism with thyroid cancer in a group of Turkish patients. Material and Methods: 58 thyroid cancer patients and 115 healthy individuals were genotyped by PCR-based RFLP analysis. Results: Polymorphic proline allele frequency was higher in patients than the controls. Pro/pro genotype was found to be a risk factor for thyroid cancer development. Arginine/proline genotype frequencies in patients and controls did not show any significant differences. There was no statistical difference between follicular adenoma and papillary carcinoma patients or TNM stages of papillary carcinoma patients for codon 72 genotypes. Discussion: Further studies involving codon 72 polymorphism of the p53 gene along with other susceptibility factors in different populations may be useful to clarify the molecular mechanisms underlying thyroid cancer development.
Tiroid kanserli Türk hastalarda p53 kodon 72 polimorfizmi
Keywords: Genel ve Dahili Tıp